Gender, gaming motives, and genre: comparing Singaporean, German, and American players - Ratan, Rabindra (2023)
This study examines gender and country differences with respect to a range of gaming motivations (e.g., social, performance, habit) and game genre choices (e.g., action, sports, casual). Surveys were conducted with 634 university students from Singapore, Germany, and the United States. Overall, the findings suggest that many game motivations and genre choices differed by player gender, country, and the interaction between gender and country in some cases. Further, game motivations and genre choices were related to each other, though sometimes in a negative direction. Finally, differences in gaming motivations, genre choices, and gender, but not the country of residence, were all found to relate to differences in future intention to play. Although these topics have been studied in isolation in previous research, the present study contributes unique insights about the intersections of gender, cultural background, gaming motivations, and genre choices.